2008
DOI: 10.1177/089686080902900208
|View full text |Cite
|
Sign up to set email alerts
|

Previous Comorbidity and Lack of Patient Free Choice of Technique Predict Early Mortality in Peritoneal Dialysis

Abstract: Objective To study the prognostic factors for mortality and hospital admission for patients on peritoneal dialysis (PD). Method Biannual data on individual characteristics, clinical and analytical progress, treatment, and events were studied for a cohort of incident patients undergoing PD (2003-2006) in a reference area of 8.8 million people. Results 489 patients (age 53.58 years, 61.6% male) with 3-year follow-up were included. They presented at inclusion with Charlson Comorbidity Index (CCI) of 5.25; previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 33 publications
(40 reference statements)
2
11
0
1
Order By: Relevance
“…It is, therefore, important to ensure that patients still have a choice of treatment, as forcing patients to choose home dialysis would not be successful and may result in increased overall costs and exacerbate treatment inequity. [24][25][26] Chronic conditions impose significant economic hardship to patients. [27][28][29] Economic hardship is exacerbated by ineligibility for government support, health service inflexibility, and low health literacy and may lead to patients not being able to effectively choose or engage in self-management.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, important to ensure that patients still have a choice of treatment, as forcing patients to choose home dialysis would not be successful and may result in increased overall costs and exacerbate treatment inequity. [24][25][26] Chronic conditions impose significant economic hardship to patients. [27][28][29] Economic hardship is exacerbated by ineligibility for government support, health service inflexibility, and low health literacy and may lead to patients not being able to effectively choose or engage in self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been performed evaluating PD patients. Most previous studies only reported a list of prognostic factors 15 , 16 , 18 , 23 - 25 and comorbidities 26 - 28 . We established a prognostic model of short-term mortality using common clinical factors associated with the prognosis of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who lack control over modality selection have worse outcomes, probably due to resistance to training and nonadherence to treatment. 7,8 Those who are less motivated, therefore, are likely to require extra training to successfully make the transition to home HD.…”
Section: Patient Selection For Home Hdmentioning
confidence: 99%